PENINGKATAN KETERAMPILAN MENULIS TEKS DESKRIPSI DENGAN MODEL THINK TALK WRITE (TTW) DI KELAS V SD NEGERI 20 KURAO PAGANG - Ramadhani, Anisya; Ari Suriani; Azmi Alwi, Nur; M. Habibi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low descriptive text writing skills of students. The problems found were that students had difficulty organizing writing outlines, as well as improper use of vocabulary and punctuation. The purpose of this study was to describe the planning, implementation, and improvement of descriptive text writing skills through the application of the Think Talk Write model. This study used a mixed-method approach, namely qualitative and quantitative, with the type of Classroom Action Research. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects consisted of 30 students. Data were collected through observation, tests, and assessment of students’ writing results, and analyzed qualitatively and quantitatively. The results showed that the teaching module in cycle I obtained an average of 87.49%, increasing in cycle II to 100%. The implementation of learning in the teacher aspect in cycle I obtained an average of 88.99%, increasing in cycle II to 96.42%. The student aspect in cycle I obtained an average of 87.49%, increasing in cycle II to 96.42%. Students’ writing skills in cycle I obtained an average of 66.16, increasing in cycle II to 83.74%. Students’ knowledge assessment in cycle I obtained an average of 70.33%, increasing in cycle II to 88%. Thus, it can be concluded that the Think Talk Write model can improve students’ writing skills outcomes in Indonesian language learning in grade V of SDN 20 Kurao Pagang, Nanggalo District, Padang City.